2020
DOI: 10.1097/md.0000000000021688
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence, death risk, and related factors in patients with stage 0 colorectal cancer

Abstract: In this study, the National Health Insurance Research Database of Taiwan was used to examine the recurrence and death risk for stage 0 colorectal cancer patients. We examined stage 0 colorectal cancer patients to identify factors causing recurrence and death. This is a retrospective study, and stage 0 colorectal cancer patients that are registered in the Taiwan Cancer Registry of the Health Promotion Administration in 2007 to 2012 were included. The database was linked to the National Health Insuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The analysis results in Table 4 showed that the risk of developing non-CRC and CRC, compared to normal diagnoses, was higher in males than in females, which is consistent with previous study findings [23,26,52]. Therefore, male patients with positive FOBT results should be cautious of the follow-up risk of developing colorectal cancer and colorectal cancer diagnosis and treatment.…”
Section: Factors That Affect the Diagnosis Of Cases With Positive Fob...supporting
confidence: 88%
See 2 more Smart Citations
“…The analysis results in Table 4 showed that the risk of developing non-CRC and CRC, compared to normal diagnoses, was higher in males than in females, which is consistent with previous study findings [23,26,52]. Therefore, male patients with positive FOBT results should be cautious of the follow-up risk of developing colorectal cancer and colorectal cancer diagnosis and treatment.…”
Section: Factors That Affect the Diagnosis Of Cases With Positive Fob...supporting
confidence: 88%
“…The analysis of the region of the medical unit that conducted follow-up examinations showed that positive FOBT cases were mostly in Northern, Central, and Southern Taiwan. Because of the predominance of metropolitan areas, demographic characteristics, and medical accessibility in the three regions [26,[37][38][39][40][41][42][43], the willingness and behavior of FOBT-positive groups to be followed up has increased, which in turn influences the distribution of diagnosis. The actual number of FOBT-positive cases in the 50 years and 71-75 years population who underwent FOBT was lower than in other age groups (Table 1), thus the number of cases diagnosed was low.…”
Section: Correlation Between Diagnosis and Positive Fobt Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor is the ongoing scientific debate regarding lifestyle, comorbidities, and recurrences wherein some studies suggest that comorbidity is also associated risk of recurrence and poorer survival. [ 43 , 44 ] Moreover, patients with higher ASA scores will less likely be found eligible for adjuvant chemotherapy. Therefore, analyzing disease recurrence in light of these abovementioned competing risks is important.…”
Section: Discussionmentioning
confidence: 99%
“…The TwCR has record completeness of 98.4%, and it has been regarded as one of the world's highest-quality cancer registries [26]. Furthermore, since 2002, the TwCR has established a long-form database including cancer staging, detailed initial treatment, and recurrence information, which researchers have widely used for cancer recurrence studies [27]. In addition, the dataset provided demographic information and medical records of patients for further analysis, such as age, sex, date of birth, death, causes of death, cancer stage, recurrence condition, disease diagnosis, and inpatient and outpatient department prescriptions.…”
Section: Data Sourcementioning
confidence: 99%